THE INFLUENCE OF STEAM-BASED PROJECT MODEL ON FIFTH GRADE ELEMENTARY STUDENTS' SCIENCE PROCESS SKILLS - Trivena; Lolotandung, Reni (Jurnal Cakrawala Pendas, 2024)
This study aims to determine whether the Science Technology Mathematics Art and Technology (STEAM) project-based model influences the Science Process Skills (SPS) of elementary school students. The research method employed is quantitative research with a one-group pretest-posttest design. The population and sample of the study were fifth-grade students from SDN 6 Saluputti, Saluputti District, Tana Toraja, totaling 21 students. The research instruments used were multiple-choice and essay tests developed from science process skill indicators on the topic of heat transfer, teacher and student activity observation sheets, and interview guidelines. The results of the study indicate a significant influence of the STEAM-based project model on the Science Process Skills (SPS) of fifth-grade elementary students with a significance value of 0.001 < 0.05, thus accepting the alternative hypothesis (Ha) and rejecting the null hypothesis (H0). The data obtained will be analyzed using Paired Sample t-Test.. The N-gain value falls into the moderate category, leading to the conclusion that there is an influence of the STEAM-based project model on the SPS of fifth-grade students at SDN 6 Saluputti. However, further research is still needed on other science topics in elementary school that can be taught using the STEAM project-based approach to enhance students' knowledge and skills in other areas.